Self-perceived health in dental students: a cross-sectional study - Gomes, Claudia Lobelli Rangel; Chaves-Junior, Samuel de Carvalho; Gavião, Maria Beatriz Duarte (Journal of Health & Biological Sciences, 2020)
Objective: this is a cross-sectional descriptive study, with the objective of verifying the relationship between health self-perception, sociodemographic characteristics, weight status and physical and psychological symptoms in a group of dental students. Methods: one hundred and sixty individuals from a Dental School, aged 16-24 years, participated. Questionnaires were applied for socioeconomic characteristics, psychological symptoms, and self-perception of health. Clinical examinations were performed to evaluate oral health (CPOD index, frequency of brushing and dental consultations) and weight status (Body Mass Index, BMI). The data were analyzed by descriptive statistics, Student t, Mann-Whitney, chi-squared tests and logistic regression. Results: the prevalence of overweight/obese individuals was 29%, with a similar proportion for the sexes (P=0.23). Weight status, satisfaction with body image, comparison with others, feeling depressed or nervous, and eating habits were factors associated with self-perception of health (OR 0.20-5.19, P < 0.05). Individuals who were satisfied with their body image or considered their eating habits healthy were more likely to perceive health positively (OR = 4.24 e OR = 4.27). Conclusion: socio-demographic characteristics showed no influence on self-perception of health, except weight status that was negatively associated with self-perception of health. Individuals who show satisfaction with their body image and consider themselves to have healthy eating habits perceived their health positively.